1995
DOI: 10.1002/jat.2550150315
|View full text |Cite
|
Sign up to set email alerts
|

Serum biochemical and histopathological changes related to the hepatic function in pigs following atrazine treatment

Abstract: Biochemical and histopathological parameters of the hepatic function were used to quantify the hepatotoxic effects of atrazine in female pigs (gilts) undergoing intensive breeding. Female pigs (cross-bred Swedish and German landrace) received 2 mg atrazine kg-1 body wt. in feed daily during 19 days of the oestrous cycle. The last treatment day corresponded to day -3 of the onset of the next expected oestrus. Blood samples were collected three times daily at 3-h intervals on the first four post-treatment days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Liver is an essential organ involved in the metabolism of exogenous toxic substance and also a primary target of ATR toxicity. It is known to cause hepatic damage in frogs, fish, birds, pigs, and rodents . The use of histologic and ultrastructural analysis allowed for the damage of target organelle in the microsomes by exposure to ATR .…”
Section: Discussionmentioning
confidence: 99%
“…Liver is an essential organ involved in the metabolism of exogenous toxic substance and also a primary target of ATR toxicity. It is known to cause hepatic damage in frogs, fish, birds, pigs, and rodents . The use of histologic and ultrastructural analysis allowed for the damage of target organelle in the microsomes by exposure to ATR .…”
Section: Discussionmentioning
confidence: 99%
“…Liver is viewed as a primary organ for atrazine metabolism, which is known to cause hepatic damage in mammalian [15, 43, 44]. However, whether the effects of atrazine have the potential influence to the cardiac and hepatic function of birds still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[12] It is known to cause hepatic damage in rats and pigs;[131415] disrupt the functioning of the reproductive tissues;[161718] cause DNA damage and genotoxicity in the stomach, kidney, and liver of rats;[1920] damage rat erythrocytes[21] as well as induce oxidative stress in several experimental models. [8212223] We previously reported that ATZ at a dose of 120 mg/kg induces oxidative stress in rat tissues and blood at 16 days of treatment, and that the oxidative stress was associated with increased lipid peroxidation and changes in the antioxidative system.…”
Section: Introductionmentioning
confidence: 99%